2007
DOI: 10.1007/s10615-007-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

The Unbearable Fatigue of Compassion: Notes from a Substance Abuse Counselor Who Dreams of Working at Starbuck’s

Abstract: Current research has determined that a larger percent of social workers and other counselors are affected by PTSD types of symptoms when working with traumatized clients than the general population. While much of this research addresses workers in specific trauma areas like sexual assault centers or child welfare agencies, little specific thought has been given towards the special stress that working with Substance Abuse Disorders (SA) and trauma may present. This paper takes a brief look at the issues of vica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…While Indigenous workers reported greater work/life imbalance they also reported high levels of co-worker support which may be effective in ameliorating workrelated strain. As other studies have found (e.g., Ducharme, Knudsen, & Roman, 2007), co-worker support appears to mitigate against stress and burnout, and in addressing vicarious trauma and emotional fatigue (Fahy, 2007) among drug and alcohol workers.…”
Section: Emotional Exhaustionsupporting
confidence: 55%
“…While Indigenous workers reported greater work/life imbalance they also reported high levels of co-worker support which may be effective in ameliorating workrelated strain. As other studies have found (e.g., Ducharme, Knudsen, & Roman, 2007), co-worker support appears to mitigate against stress and burnout, and in addressing vicarious trauma and emotional fatigue (Fahy, 2007) among drug and alcohol workers.…”
Section: Emotional Exhaustionsupporting
confidence: 55%
“…2 By engaging in empathic relationships with patients, helping professionals such as family physicians undergo a transformation in their inner experiences that impacts emotions and cognitive patterns. 3,4 Far from being pathologic, VT is a normal part of any caring professional's emotional response. Just as trauma symptoms are a normal response to a traumatic event, VT is a normal response to working with traumatized patients.…”
mentioning
confidence: 99%
“…2 Identification of VT is important because if left unchecked, it can lead to a specific form of burnout often referred to as compassion fatigue (CF). [3][4][5][6][7] Although VT is a normal part of the work, CF is not inevitable and can be prevented. 8,9 This qualitative study set out to explore the phenomenon of VT in a group of inner-city family physicians caring for a patient population known to experience high levels of trauma: women using illicit drugs.…”
mentioning
confidence: 99%
“…CF may in turn also have an adverse effect on the way HCS may view their work and the clients they serve (Germer, 2009;Tehrani, 2010). Fahy (2007) suggests that burnout can have a blaming component to it and the unspoken message is that if you are burned out it is already too late. She proposes that CF may be a more useful term to encourage dialogue between workers and supervisors to enable them to decide on solutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The term Compassion Fatigue (CF) has been offered as a way of describing what may happen to a HCS over time (Fahy, 2007). There are a number of studies that focus on the negative cost of caring (Boisaubin and Levine, 2001;Gilroy, et al, 2002;Smith and Moss, 2009), however, there is also evidence to show that HCS can transform the stress of this type of exposure into growth.…”
Section: Introductionmentioning
confidence: 99%